A Parallel Computing System - Roitman, Jorge V. (My University, 1972)
A highly parallel computing system capable of computing transcendental functions, matrix operations and iterative calculations has been devised and a typical cell has been implemented. The system consists of an array of cells, a control unit, a PDP-11 computer and an interface unit. The array uses modified SOLOMON type of communication between cells. Each cell consists of 15 words and arithmetic hardware. Arithmetic and logic operations, on words or bytes, may be performed serially between pairs of these words. Division and floating-point arithmetic are under software control. Parallel algorithms have been developed. A set of instructions and mnemonics permits a practical use of the system. The possibility of using the array as an associative-memory processor is also considered. The system has been tested by using the software package prepared. Although only one cell has actually been constructed a complete array has been simulated on a PDP-11 computer.
Keywords: parallel, computing, system, array, cells, matrix